Effet de la fertilité du sol et du stress hydrique sur Banana Bunchy Top Disease - Rolande, Amossou R.; Euloge, Togbe; Omondi, Bonaventure Aman Oduor (2022)
Early detection is important for the management of the Banana Bunch Top Disease (BBTD) as it enables the removal of inoculum and hence propagation of the disease. Roguing has been demonstrated as an effective way of managing BBTD if done consistently and in time. Disease detection is however dependent on the clear expression of the disease and its relationship with the onset of secondary spread from newly infected plants. Seasonal variations in BBTD cases observed in fields has been reported previously. This study investigated the effect of water stress and nutritional status of the soil on the expression of BBTD in two cultivars of Banana: FHIA 25 (hybrid) and a local landrace cultivar, Soutoumon. The two had previously been shown to differ in their response to symptom development. In brief we observed a delay in BBTD symptom expression associated with water stress under low fertility for both cultivars. Similar to previous reports, FHIA expressed the disease earlier than Soutoumon. Note: The poster is presented in French